Treating Intimal Injury to the Graft Hepatic Artery by Intraoperative Fluorescence Vascular Stenting. Issue 2 (August 2019) - Hsieh, Chia-En; Chen, Yao-Lin; Lin, Kuo-Hua; Chou, Chen-Te; Hsu, Ya-Lan; Chen, Chia-Bang; Lin, Ping-Yi; Lin, Shin-Lung
Abstract : Background: Early hepatic artery (HA) thrombosis and primary graft failure contribute greatly to the mortality of patients after liver transplantation. Herein, we present the treatment of intimal injury of HA by intraoperative fluorescence vascular stenting. Methods: A sample of 471 patients receiving liver transplantations underwent arterial anastomosis. Six patients (1.3%) were found to have early HA thrombosis. Two patients had thrombi that were impenetrable with a guide wire. Intimal injury on both the graft and the donor sides of the HA was found after thrombectomy. We performed anastomosis between unhealthy graft vessels and healthy recipient vessels. Intraoperative angiography was done immediately because of the guide wire being easier to insert through a fresh thrombus, and a long endovascular stent was inserted to bypass the injured vessels. Results: The proper HA was reconstructed under microscopy. Three days after reconstruction, an angioplasty showed no dissection, stenosis, or pseudoaneurysm of the HA. Unexpectedly, these 2 patients survived well with acceptable graft functionality, one based on a 32-month follow-up and the other based on a 2-month follow-up. Conclusion: Anastomosis of the intimally injured graft artery followed by immediate endovascular angioplasty with stenting to bypass the injury zone is an efficacious and tolerable procedure.